Description of the last-instar larva of Zenithoptera lanei Santos, 1941 (Odonata: Libellulidae) - Rippel, Camila G.; Neiss, Ulisses G.; Del Palacio, Alejandro; Schröder, Noelia M.; Fleck, Günther; Hamada, Neusa; Martí, Dardo A.; Schweigmann, Nicolás J. (Zootaxa, 2020)
The larva of Zenithoptera lanei Santos, 1941 is described and illustrated based on three exuviae of reared larvae collected in Misiones, Argentina, Roraima and Amazonas, Brazil. A comparison with the larva of Z. anceps Pujol-Luz, 1993 is included.